Desenvolvimento e reúso de frameworks com base nas características do domínio - Viana, Matheus Carvalho (2014)
Frameworks are software artifacts that implement the basic functionality of a domain. Its reuse can improve the efficiency of development process and the quality of application code. However, frameworks are difficult to develop and reuse, since they require a complex structure to implement domain variability and be adaptable enough to be reused by different applications. Due to these difficulties, this research presents two approaches: 1) the From Features to Frameworks (F3) approach, in which the developer models the features of a domain and a pattern language helps in implementing a framework based on this model; and 2) the approach that uses a Domain-Specific Language (DSL) built from the identification and analysis of the domain features of a framework to facilitate the reuse of this framework. A tool, called From Features to Frameworks Tool (F3T), was also developed to support the use of these two approaches, providing editors for modeling domains and applications and automating the implementation of code of frameworks, DSLs and applications. In addition to facilitate the development and reuse of frameworks, experiments conducted during this project showed that these two approaches make these processes more efficient and allow the construction of frameworks and applications with less difficulty.